2003
DOI: 10.4148/1090-7025.1029
|View full text |Cite
|
Sign up to set email alerts
|

Kansas Case Study Applications of Nitrogen-15 Natural Abundance Method for Identification of Nitrate Sources

Abstract: The nitrogen-15 natural abundance method has been a tool for identifying sources of nitrate contami nation in groundwater for almost 30 years. Different ranges of δ 15 N in groundwater are associated with different sources such as fertilizer and animal wastes. However processes such as denitrification, nitrification, and volatilization can alter the δ 15 N signature.Use of this method in Kansas has had mixed results. One case study documented in this paper showed the utility of the method in an area with a san… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…Natural abundance stable isotopes are effective tools for elucidating biogeochemical processes in microbial ecology (Högberg, 1997;Robinson, 2001;Boschker & Middelburg, 2002;Staddon, 2004). Exploiting differences in isotope signatures between nutrient source and sink has made it possible to link microbial activity to ecosystem processes (Miyazaki et al, 1980;Orphan et al, 2001;Townsend et al, 2003). Ecosystem ecologists are increasingly interested in measuring the natural abundance isotopic composition of the microbial biomass or DNA extracted from the environment in order to interpret dominant microbial processes (Dijkstra et al, 2006a, b;Schwartz et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Natural abundance stable isotopes are effective tools for elucidating biogeochemical processes in microbial ecology (Högberg, 1997;Robinson, 2001;Boschker & Middelburg, 2002;Staddon, 2004). Exploiting differences in isotope signatures between nutrient source and sink has made it possible to link microbial activity to ecosystem processes (Miyazaki et al, 1980;Orphan et al, 2001;Townsend et al, 2003). Ecosystem ecologists are increasingly interested in measuring the natural abundance isotopic composition of the microbial biomass or DNA extracted from the environment in order to interpret dominant microbial processes (Dijkstra et al, 2006a, b;Schwartz et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…In a study conducted in Runnels County in Texas, Kreitler and Jones (1975) concluded that about 66% of the NO 3 in groundwater had natural sources. In general, the δ 15 N values of N from commercial fertilizers, soil, precipitation, and animal wastes range from −7 to +8‰, +5 to +7‰, 12 to +3‰, and greater than +10‰, respectively (Kellman and Hillaire‐Marcel, 2003; Townsend et al, 2003). However, considerable overlap in δ 15 N between N sources makes their accurate identification difficult using N isotopes.…”
mentioning
confidence: 99%
“…Animal waste has a high ammonia component and because of the preferential release of 14 N by the volatilization of ammonia (Kreitler, 1975), the remaining nitrogen becomes enriched in δ 15 N to a value of +10‰ or more. Generally in Kansas, with animal-waste sources, nitrate-N values are commonly more than 10 mg/L and δ 15 N values are above +10‰ (Townsend et al, 2003).…”
Section: Nitrogen-15 Natural Abundance Isotope Methodsmentioning
confidence: 99%